Discovery of 2-(4-sulfonamidophenyl)-indole 3-carboxamides as potent and selective inhibitors with broad hepatitis C virus genotype activity targeting HCV NS4B. Issue 2 (15th January 2016) - Zhang, Nanjing; Turpoff, Anthony; Zhang, Xiaoyan; Huang, Song; Liu, Yalei; Almstead, Neil; Njoroge, F. George; Gu, Zhengxian; Graci, Jason; Jung, Stephen P.; Pichardo, John; Colacino, Joseph; et al.
Graphical abstract: Abstract: A novel series of 2-(4-sulfonamidophenyl)-indole 3-carboxamides was identified and optimized for activity against the HCV genotype 1b replicon resulting in compounds with potent and selective activity. Further evaluation of this series demonstrated potent activity across HCV genotypes 1a, 2a and 3a. Compound4z had reduced activity against HCV genotype 1b replicons containing single mutations in the NS4B coding sequence (F98C and V105M) indicating that NS4B is the target. This novel series of 2-(4-sulfonamidophenyl)-indole 3-carboxamides serves as a promising starting point for a pan-genotype HCV discovery program.